The host range and distribution pattern of rhizocephalan parasitic barnacles in Korean coasts and their relationship with geographical factors - Jung, Jibom (Frontiers in Marine Science, 2024)
This study provides a comprehensive analysis of the host range and distribution patterns of Rhizocephala, specialized parasitic barnacles, in Korean waters. Utilizing morphological and molecular techniques, including mtDNA cox1 sequencing, this study identifies 26 rhizocephalan species parasitizing 28 decapod hosts. Notably, it uncovers three previously unreported parasitehost relationships. While three rhizocephalan species infect three or more hosts, the majority are associated with one or two hosts, with geographical variations in host-parasite relationships suggested. The study also reveals regional differences in Rhizocephalan diversity across three Korean marine ecoregions, with the highest diversity in the East China Sea ecoregion, likely due to warmer winter water temperatures. In contrast, lower diversity in the Yellow Sea and East Sea ecoregions is attributed to colder winter temperatures. These findings highlight the importance of further taxonomic research on Rhizocephala and their hosts to enhance understanding and management of these ecologically and economically important parasites.